RELEVANSI HAK HUKUM DAN KEWAJIBAN BERMASYARAKAT DALAM MEWUJUDKAN KEADILAN DI ERA DIGITAL - Ramlin Ahmad; Fitriyadi (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
The rapid development of digital technology has transformed social interaction and legal relations, creating challenges in balancing legal rights and civic obligations. This article analyzes the relationship between legal rights and civic duties in the digital era, particularly concerning social order, digital justice, and legal awareness. The study employs a descriptive qualitative method with a normative-sociological approach, examining statutory regulations, legal doctrines, and digital social phenomena. The findings indicate that an imbalance between the exercise of digital rights and the fulfillment of legal obligations contributes to privacy violations, misuse of freedom of expression, and low compliance with legal norms. Limited digital legal literacy and regulatory complexity also hinder effective law enforcement. The study concludes that strengthening digital legal education, improving regulatory frameworks, and promoting ethical digital conduct are essential to fostering a balanced, responsible, and just digital society.